Development of a traffic congestion index for Singapore - Wang, Lida. (2008)
This thesis provides the concept of deriving congestion index based on traffic information, and develops an analytical tool for accessing traffic congestion, which can be communicated to non-technical users. The project makes use of existing traffic data collected every 6 months by the Land Transport Authority (LTA) of Singapore.